Development of near real-time assessment system for cancer cells / Nahrizul Adib Kadri - Nahrizul Adib, Kadri (2010)

(untitled)
Dielectrophoresis (DEP) is an electrical phenomenon that occurs when a polarisable particle is placed in non-uniform electrical fields, generating DEP force (FDEP) that is dependent upon the electrophysiological make-up of the particle in use. In cell cytometry studies, DEP offers the advantage of conducting various cell manipulations in vitro without the need of specific surface markers. Its drawbacks, namely the time-consuming processes involved and the inability to conduct large batch cell assays, had limited its usage. This thesis presents the work that offered solution to the said obstacles, by developing a system capable of conducting DEP experiments within a very short period of time, thus allowing DEP effects to be recorded close to real-time; and conducting the DEP experiments in parallel, thus allowing the DEP effects to be recorded concurrently on multiple cell samples. This is achieved with the design and development of programmable, multiple output waveform generator using (capable of producing up to eight signal outputs, and extendable in multiples of four channels); improvement of planar microelectrode device design (capable to be energised individually); design and fabrication of the microfluidic gasket (better solution flow without localised cell collections), and design and development of alternative DEP image analysis algorithms (capable of handling near real-time DEP events data, and quantifying initial conditions for the light intensity). Results from the validation studies showed that the waveform generator is capable of producing stable, individually addressed channel outputs of up to 10 MHz at 15 Vp-p with the DEP effects observed when the signal is supplied at a minimum of 10 seconds. The system is also capable of handling highly conductive suspending media (up to 1.4 S/m). Validation studies using leukemic cell lines showed the system is capable of producing near real-time DEP spectra that were consistent with published data at a minimum temporal resolution of 60 seconds. DEP effects of the said cell population when treated with valinomycin, a K+ ionophore, were also recorded and showed a decrease of both membrane conductance and capacitance values as apoptosis was induced and progressed. Declaration of Originality This thesis and the work to which it refers are the results of my own efforts. Any ideas, data, images or text resulting from the work of others (whether published or unpublished) are fully identified as such within the work and attributed to their originator in the text, bibliography or in footnotes. This thesis has not been submitted in whole or in part for any other academic degree or professional qualification. I agree that the University of Surrey has the right to submit my work to the plagiarism detection service TurnitinUK for originality checks. Whether or not drafts have been so-assessed, the University reserves the right to require an electronic version of the original document (as submitted) for assessment as above